FORMATION OF LITERACY SKILLS IN PRESCHOOL CHILDREN - Yakubova Gulnoz Madrimboyevna (Bright Mind Publishing, 2025)
This article explores the formation of literacy skills in preschool-aged children, emphasizing the importance of early language exposure, phonological awareness, and cognitive development. It reviews current literature on pre-literacy development, outlines effective pedagogical strategies, and presents results from observational studies and educational interventions. The study highlights how structured and play-based learning environments contribute to a child's readiness for reading and writing, offering recommendations for educators and caregivers.
Keywords: Preschool education, literacy skills, phonological awareness, emergent literacy, early childhood development, language acquisition, cognitive readiness.